Incorporating Environmental, Social and Governance (ESG) Standards into Corporate Strategies for Success: A Case Study of a Group of American Companies (International Journal of Financial, Administrative and Economic Sciences, 2024)
Success and growth are important goals to ensure survival, leadership, and sustainability of companies in the market. These goals require thoughtful strategic decisions that consider the company's impact on its environment and society besides balancing its profitability with social responsibility. This research aims to study how companies adopt ESG standards and incorporate them into strategic plans, and how that affects their stock performance in the financial market as criteria for companies' success. A sample of (45) USA companies adopting ESG standards was selected for this study. Simple linear regression analysis was used to show the relationship between ESG scores and indicators such as( Composite Rating, Relative Strength, and Earnings per Share Rating), according to the Investor's Business Daily (IBD) classification. The Composite Rating (Comp Rtg) reflects the overall performance level of the company’s stocks based on fundamental and technical analysis compared to other stocks in the same industry, the Relative Strength Rating (RS Rtg) compares the company's stock price performance against the overall market performance, while the Earnings Per Share Rating (EPS Rtg) reflects the profit that each share achieves, which significantly affects sustainable growth and success. The study results showed a significant impact of ESG on the Composite (Comp) Rating and a weak impact on the Relative Strength  (RS) and Earnings Per Share (EPS)  Ratings, which may be attributed to other market-related factors. These results can provide valuable insights for companies looking to improve their long-term value by investing in sustainable practices and attracting socially responsible investors, thus enhancing their performance and competitive advantage in the market.
Keywords: Corporate Strategies; Sustainable Practices; Governance Practices; Environmental; sustainable success